Brak wiedzy o rynku jako bariera efektywnego wykorzystania środków wspólnotowych - Potwora, Witold (Lack of Knowledge about the Market as a Barrier of an Effective Use of the European Union Means, 2006)
The article discusses the necessity of stronger participation of market researchers in the process of preparation and implementation of region development strategy. The analysis was carried out in the aspect of gaining and allocating European Union funds procedure. The author concentrates especially on three problems: The role of market information in the objectivization of SWOT analysis; Using the knowledge about the market in the procedures of evaluating the development programme of micro and small enterprises; The role of market researches in the implementation of coherent and equal chances policies.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1107, s. 167-176